Pengembangan Bisnis UMKM Rumah Komunitas - Agus Sutardi; Dellya Putri; Kania Kania; Nazillah Layla Nur K; Novia Wulan (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
The aim of this research is to determine the development of business feasibility studies for Community House MSMEs. This research uses descriptive qualitative research methods. The object of this research is Community House MSMEs. The results of this research are that Rumah Masyarakat MSMEs have a business license and are legally registered, the market and marketing aspects of Rumah Masyarakat have good market and marketing strategies so that now their products have been sold to various regions in Indonesia and even abroad such as Malaysia and Singapore, from the technical and technological aspects, community houses also have a system that runs well so that production and sales activities run smoothly, then the management aspect of Community Houses has a clear organizational structure and job description and also has definite criteria for recruiting candidates. employees, from the financial aspect Rumah Masyarakat started its business with the trust of its relationships, and as seen from the income and sales of RumahCommunity products which continue to increase, RumahCommunity can be said to be feasible and successful in running its business.